Thiazoles: A Retrospective Study on Synthesis, Structure-activity Relationship and Therapeutic Significance - Sharma, Shivkant; Devgun, Manish; Narang, Rakesh; Lal, Sukhbir; Rana, Avtar Chand (Indian Journal of Pharmaceutical Education and Research, 2022)
Thiazole or 1,3-thiazole is a distinct heterocyclic compound which incorporates sulphur and nitrogen atoms. It is a vital framework present in numerous pharmacologically active compounds, be it of natural origin or of synthetic nature. Many thiazoles having antitumor and antiviral activities, originate from microbes and marine organisms. A variety of synthetic drugs, having thiazole group, like antimicrobial sulfathiazole, antibiotic penicillin, antidepressant pramipexole, antineoplastic agent bleomycin, antiretroviral drug ritonavir, histamine H2 receptor antagonist nizatidine, anti-inflammatory drug meloxicam, antifungal stilbene derivatives have been in the markets for quite some time. Hofmann and Hantzsch laid the groundwork for further development in the field of thiazole chemistry. The interaction of α-haloketones or α-halogenaldehyde and thioamide to obtain thiazoles is beautifully described by Hantzsch. Various studies have reported methods for the synthesis of the thiazoles; thioforamide, thiourea, α-thiocyanotoketones, and vinyl bromide have been extensively employed to synthesize thiazoles. The thiazoles have immense potential and this study tries to enlighten the crucial role of thiazoles for the betterment of society. The review provides different directions in the synthesis of novel thiazoles and also reveals diverse targets for augmentation in the field of designing of novel thiazoles.
Keywords: Thiazoles; Synthesis; QSAR; Molecular Docking; Biological Activity